Collaboration between Parents and Teachers on Early Childhood Character Development - Saudah, Saudah; Iskandar, Ali; Hidayati, Sri; Puspita, Dwi (Cakrawala: Jurnal Pendidikan, 2025)
Early childhood character education is a challenge amidst the moral decline of the nation's children. This study highlights the importance of collaboration between parents and teachers in shaping children's character. This quantitative research with correlational method analyzes the relationship between parent collaboration, teacher collaboration, and early childhood character development. The study population consisted of early childhood, parents, and teachers in several PAUD and TK institutions, with a sample of 20% of the total population. Data collection was conducted through a structured questionnaire with indicators of communication, involvement, and moral support from parents, as well as planning, implementation, and evaluation by teachers. The analysis showed that collaboration between parents and teachers significantly contributed to children's character development, including cognitive, affective and psychomotor aspects. Teacher collaboration has a greater influence than parents. This study emphasizes the importance of synergy between families and schools in creating a learning environment that supports early childhood character development.